The Effect of Preoperative Ketamine Gargles on Postoperative Sore Throat After Oral Endotracheal Intubation in Patients Undergoing Laparoscopic Cholecystectomy - Safir, Saad Salman; Shafiq, Mohammad; Ali, Amber; Bakhtiar Khan, Muhammad Yahya; Khan, Shaharyar (Biological and Clinical Sciences Research Journal, 2025)
Postoperative sore throat (POST) is a common and distressing complication following general anesthesia with endotracheal intubation, particularly in laparoscopic surgeries. Various interventions have been explored to reduce POST, with ketamine gargles emerging as a potential prophylactic agent due to its local anti-inflammatory and analgesic effects. Objective: To evaluate the efficacy of preoperative ketamine gargles in reducing the incidence and severity of postoperative sore throat and throat pain in patients undergoing laparoscopic cholecystectomy. Methods: This randomized controlled trial was conducted at a tertiary care hospital between 1st July 2024 to 31st December 2024. Seventy adult patients (ASA I–II) scheduled for elective laparoscopic cholecystectomy under general anesthesia were randomized into two groups (n=35 each): Group K (ketamine gargle) and Group C (control gargle). Participants received a 30-second gargle solution preoperatively. The primary outcomes were the incidence of sore throat and throat pain within 24 hours post-extubation. Secondary outcomes included the occurrence of cough, hoarseness, hemodynamic variations, and any adverse effects. Statistical analyses, including multivariable logistic regression, were conducted using SPSS, with significance set at p<0.05. Results: Out of 70 patients, 40 (57.1%) were female with a mean age of 44.9 ± 10.1 years. Ketamine gargle significantly reduced the incidence of sore throat (11.4% vs. 45.7%, p = 0.002) and throat pain (8.6% vs. 31.4%, p = 0.018) at 24 hours compared to the control group. Multivariate analysis confirmed that ketamine use was independently associated with lower odds of sore throat (aOR = 0.19; 95% CI: 0.07–0.51; p = 0.001) and throat pain (aOR = 0.22; 95% CI: 0.08–0.61; p = 0.004). No significant differences were observed in the incidence of postoperative cough or hoarseness (p > 0.05). Complications were minimal and comparable across both groups. Conclusion: Preoperative ketamine gargles are effective in significantly reducing the incidence and severity of postoperative sore throat and throat pain following laparoscopic cholecystectomy. Their use appears safe and well-tolerated, supporting the role of ketamine as a simple and beneficial prophylactic intervention.